2021
DOI: 10.1186/s13643-021-01580-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural stigma and its impact on healthcare for consumers with borderline personality disorder: protocol for a scoping review

Abstract: Background Structural stigma in health systems experienced by consumers diagnosed with Borderline Personality Disorder (BPD) is a widespread phenomenon that causes major health inequities and harm for this population. Structural stigma in this context relates to institutional policies, cultural norms, and organizational practices that limit consumers’ access to health services, quality of care, and capacity to achieve optimal health and well-being. BPD is a serious mental illness with high morb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The stigma against HIV impacts changing the life habits of PLWHA and reducing their health status. Several studies have revealed various cases of stigma affecting health practices [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…The stigma against HIV impacts changing the life habits of PLWHA and reducing their health status. Several studies have revealed various cases of stigma affecting health practices [22], [23].…”
Section: Discussionmentioning
confidence: 99%
“…A diverse range of study designs including quantitative, qualitative, mixed methods and systematic review, were included in the review. In accordance with integrative review methodology [ 39 ], this review sought to identify, synthesize, and summarize the current evidence-base on the impact of BPD-related educational interventions [ 40 ] on attitudes and practices to working with people with BPD among health practitioners from diverse disciplines, across various healthcare settings. Russell’s [ 41 ] five-stage integrative review process (problem formulation, literature search, data evaluation, data analysis, interpretation and presentation) guided the methodological rigor of this review.…”
Section: Methodsmentioning
confidence: 99%
“…The search included three categories of search key terms: (a) BPD; (b) Stigma; and, (c) Crisis care. The eligibility criteria (see Table 1 ) based on the Population-Concept-Context (PCC) framework [ 40 ] guided the study selection process during screening.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) What are the speci c drivers in uencing the manifestation and perpetuation of BPD-related structural stigma in healthcare systems, and the implications for research, policy, and practice? [91].…”
Section: Aim and Research Questionsmentioning
confidence: 99%